Citrus Pest Quick Guide: California Red Scale (Aonidiella aurantii) - X. Martini; J. Price (EDIS, 2022)
This factsheet gives the general public and citrus growers basic knowledge regarding the California red scale. Written by X. Martini and J. Price, and published by the UF/IFAS Entomology and Nematology Department, November 2022.